Corn distillers dried grains with solubles in the feed of broilers and their effects on the performance, carcass yield, and gastrointestinal characteristics - Valentim, Jean Kaique; Lima, Heder José D 'Ávila; Bittencourt, Tatiana Marques; Moraleco, Debora Duarte; Lopes, Yury Gonçalves; Antunes, Hellen Cristina Ferreira; Matos e Silva, Nayara Emanoelle; Tossué, Fernandes Jesuino Muquissai (Medicina Veterinária, 2022)
This study was conducted to determine the effect of different levels of corn distillers dried grains with solubles (DDGS) in the diet of broilers, with regard to the performance, carcass yield, and gastrointestinal characteristics. A mixed lot of 700 one-day-old broilers from the COOB 500 lineage were used. It was distributed in a completely randomized design with five treatments, seven repetitions, and twenty broilers per experimental unit — ten male and ten female. The DDGS levels studied were inclusion of 4%, 8%, 12%, and 16% on experimental diets, plus the control treatment (0%). The period of 1–42 days were considered for performance evaluation. For performance, the following factors were evaluated weight gain (WG) (g/bird/day), ration consumption (RC) (g/bird/day), feed conversion (FC), medium weight (MW), productive efficiency index (PEI), and viability (V). At 42 days of age, two broilers from each lot were selected, weighed, and the ones with medium weight were identified from the experimental unit, for slaughtering and evaluation of cut yield, carcass, and gastrointestinal biometry. The evaluated parameters were submitted to variance analyses with a 5% probability, using the statistical program SAS-2012. The effects of the inclusion of DDGS were estimated through variable analyses via regression models and the contrasts by the Dunnett test, with a 5% probability. In the period of 1–42 days of production, the values of better performance obtained for the variables WG, FC, MW, and PEI were at levels of 7.28%; 10.60%; 12.10%, and 12.92%, respectively. There was a reduction in carcass weight, breast, and fat of the broilers, when using 12% and 16% of DDGS. Therefore, it indicated the inclusion of up to 11.02%, and 7.44% in the diet, so there was no loss on carcass yield and breast weight, respectively.